Analisa Faktor-Faktor Yang Mempengaruhi Harga Obligasi Bank Muamalat Periode Juli 2008 - Desember 2014 - Rosida Dwi Ayuningtyas; Rindang Nuri Isnaini Nugrohowati (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
The paper attempts to analyze the influence of deposit interest rate, profit sharing, exchangerate, Jakarta islamic index, financing debt ratio, and return on equity to sharia bond price ofIndonesia muamalat bank period july2008 until December 2014. The model used is errorcorrection model (ECM), with monthly time series data sourced from Indonesia stockexchanges, central bank, and financial services authorities. The result of the analysis showthat in the short run, the rupiah exvhange rate against the US dollar has a significantinfluence on the sharia bond price of Indonesia muamalat bank with its probability value0.0068, while the long term Jakarta Islamic index has significant effect with the probabilityvalue 0.0150 to the sharia bond price of the Indonesia muamalat bank in july period 2008until December 2014Keywords: Islamic bond, Islamic bank, macroeconomic, ECM model